Vestibular atelectasis: Myth or reality?. (10th January 2019) - Eliezer, Michael; Attyé, Arnaud; Guichard, Jean‐Pierre; Vitaux, Hélène; Guillonnet, Antoine; Toupet, Michel; Herman, Philippe; Kania, Romain; Houdart, Emmanuel; Hautefort, Charlotte
Abstract : Objectives/Hypothesis: Because delayed post‐contrast three‐dimensional fluid‐attenuated inversion recovery imaging sequences enable the distinction between the utricle and the saccule, we raised the hypothesis that patients with vestibular atelectasis (VA) could show unilateral collapse of the utricle and the ampullas on imaging. Study Design: Retrospective case series. Methods: We retrospectively reviewed 200 patients who underwent 3 T magnetic resonance imaging (MRI) after intravenous administration of gadolinium. MRI scans were assessed for the presence of VA. The endolymphatic space was considered as collapsed when the utricle and at least two ampullas were not visible or were barely visible. Results: We reported four patients with VA on MRI responsible for atypical clinical presentations of acute vestibular deficit. All patients presented a specific involvement of the pars superior sensory captors (utricle, ampullas), preserving the pars inferior sensory captors (cochlea and saccule). This was confirmed both clinically and on MRI. Conclusions: Our study is the first to describe in vivo unilateral collapse of the pars superior on delayed postcontrast MRI in patients with a clinical unilateral vestibular loss. Level of Evidence: 4 Laryngoscope, 129:1689–1695, 2019